2013
DOI: 10.1021/ol401730d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biophysical Properties of Constrained d-Altritol Nucleic Acids (cANA)

Abstract: The first synthesis of constrained altritol nucleic acids (cANA) containing antisense oligonucleotides (ASOs) was carried out to ascertain how conformationally restricting the D-altritol backbone-containing ASO (Me-ANA) would affect their ability to form duplexes with RNA. It was found that the thermal stability was reduced (cANA/RNA -1.1 °C/modification) compared to DNA/RNA, suggesting the constrained system results in a small destabilizing perturbation in the duplex structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…2,11,14 Accordingly, the unsatisfactory melting profile of r-CNA could be due to the energetic penalty required for a forced conformational change from the non-hybridizing 1 C 4 form to the RNA-mimicking 4 C 1 chair (Scheme 4). As already observed for similar substrates, 15 the conformational preference of the cyclohexanyl ring is the result of 1,3-diaxial strains occurring in the 4 C 1 form among the nucleobase and the neighbouring hydrogen atoms (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,11,14 Accordingly, the unsatisfactory melting profile of r-CNA could be due to the energetic penalty required for a forced conformational change from the non-hybridizing 1 C 4 form to the RNA-mimicking 4 C 1 chair (Scheme 4). As already observed for similar substrates, 15 the conformational preference of the cyclohexanyl ring is the result of 1,3-diaxial strains occurring in the 4 C 1 form among the nucleobase and the neighbouring hydrogen atoms (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between pairing affinity of a nucleic acid and conformational preferences of the corresponding sugar moiety has been already extensively pointed out. 2,11,14 Accordingly, the unsatisfactory melting profile of r-CNA could be due to the energetic penalty required for a forced conformational change from the non-hybridizing 1 C 4 form to the RNA-mimicking 4 C 1 chair (Scheme 4). In addition, we reasoned that the same arguments could also explain the high pairing selectivity of r-CNA under mismatching conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our surprise, a striking destabilization effect was observed for both LCeNA and LCNA. Although some destabili-zation was observed by Migawa et al 25 on structural related cANA derivatives, the drop in affinity is significantly larger in this case and cannot be clarified by the explanation suggested in their work, because the repulsion of the hydrogen in the bridge and the six-membered pseudosugar ring in cANA and LCeNA should lead to opposite effects ( Fig. 4).…”
Section: Resultsmentioning
confidence: 57%
“…12,13 Recently, Seth et al have shown that 2′-fluoro hexitol nucleic acids (FHNA, 6) exhibit higher duplex stability compared to 2′-fluoro CeNA (F-CeNA, 7) due to higher rigidity and superior stabilization in C3′-endo-like conformation. 14,25 The major objective of our presented study was the preparation of hybrid derivatives merging LNAs and CeNAs in order to stabilize the cyclohexene moiety in 3 H 2 conformation resembling the C3′-endo, which is preferred by CeNA while forming a duplex with complementary RNA strands. 13 In addition, the synthesis of locked cyclohexene nucleic acid (LCeNA) monomers made it easy to obtain saturated monomers bearing a cyclohexane ring instead of the original cyclohexene one (LCNA).…”
Section: Introductionmentioning
confidence: 99%